Potential Anti-cancer and Anti-bacterial Activities of Philippine Echinoderm Extracts - Rodyl J. Layson; Maria Criselda A. Rodil; Elmer-Rico E. Mojica; Custer C. Deocaris (Journal of Tropical Life Science, 2014)
In high-throughput search for bioactive compounds under resource-limited settings from Philippine echinoderms, the aqueous, methanol, chloroform and hexane extracts of seven Philippine echinoderms namely Holothuria nobilis (sea cucumber), Bohadscia marmorata (sea cucumber), Stichopus chloronatus (sea cucumber), Holothuria axiologa (sea cucumber), Linckia laevigata (starfish), Oreaster nodusus (starfish) and Ophiocoma ochoenleinii (brittle star) were screened for antitumor and antibacterial activity. Antitumor activity was determined using brine shrimp lethality assay while antibacterial assay was performed using turbidimetric method. Both assays utilized 96-well microtiter plates to facilitate speed and ease in screening. The chloroform extract of H. nobilis gave a positive result on antitumor activity while almost all sample extracts showed antibacterial activity against E. coli.